Image and credibility of the U.S. in Europe. Irak war coverage in European TV - La-Porte, Teresa (2009)
In Iraq, political discussion is as relevant as the war itself. The controversy on the legitimacy of the “pre-emptive war” and the power of the United States to set out its specific World order marches in parallel to the military conflict. In this situation, the United States image reflected in the media, particularly on TV, is decisive to deter mine American credibility in Europe, and justifies interest in analyzing news content.